DESAIN RELIEF PILAR BANGUNAN - Djunaedi, Idam (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
Pillar is element of building it functions to support buiding; moreover it also functions to decorate the shape of building. The technique, to build model of relief surface on this pillar can be conducted by: (1) constructing  relief profile of curve shape then moving to have variation such as the thickness of different relief, highrise, concave or domeshape surface, and also multi surfaces, (2) modifying upper side shape and angulared pyramide upper side and also building highrisely with resulted in several various models such as contributing multi shape surfaces (concave, domeshape, spinning model) and highrising with first level in the form of angulared pyramides and the second level can be filled one, four, and five of pyramide or ball part; (3) constructing tube part and ellips pieces if it is given different radiant on that tube it will result in the different thickness, if four pieces of ellips come up from the same center then they are interpolited, it will be found different multi domeshape. Fill in several models of the above result into surface matrix of terrace pole. The fulfillment surface matrix of terrace pole contributes various simetrical model (one simetrical axis, two simetrical axis, and in-line simetric) which can shape the beauty of terrace pole.